Parking data analysis - Ahamed, Kasfi; Haque, Fardin; Rasheed, Ahnaf Ar; Rahman, Md. Arban (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.